Spatiotemporal profiles of ultrafine particles differ from other traffic-related air pollutants: lessons from long-term measurements at fixed sites and mobile monitoring. Issue 7 (14th October 2021) - Gani, Shahzad; Chambliss, Sarah E.; Messier, Kyle P.; Lunden, Melissa M.; Apte, Joshua S.
Abstract : We use long term fixed site measurements along with extensive mobile monitoring data to evaluate the spatiotemporal correlation of UFP and NO x . Abstract : In the absence of routine monitoring of ultrafine particles (UFP, D p < 100 nm), air pollution epidemiology studies often use other co-emitted pollutants as a proxy for UFP, with NO x (NO + NO2 ) considered a good choice. We use long term fixed site measurements along with extensive mobile monitoring data to evaluate the spatiotemporal correlation of UFP and NO x . We incorporate 6 years of hourly particle number (PN, an approximation of UFP) concentration data from multiple fixed sites across the San Francisco Bay Area that include near-highway, urban, suburban, and rural sites. In addition, we incorporate observations from a 32 month mobile monitoring campaign comprising >1000 h of coverage of a range of road types and land uses. Across all fixed sites, PN concentrations show prominent mid-day peaks during the summer – characteristic of new particle formation – which are not observed for other co-emitted pollutants (NO x, BC, CO). While we find moderate correlation in diurnal patterns of NO x and UFP at sites with high traffic, the correlation drops significantly for low traffic areas, especially during high insolation ( e.g., summer daytime) periods. Mobile monitoring data yields similar results: NO x is observed to have weaker correlation with PN for non-highway roads during high insolation periods. The spatiotemporal profiles of UFP can differ strongly from other co-emitted air pollutants when new particle formation contributes a significant share of UFP.